KONSEP AL-MADINAH AL-FADILAH AL-FARABI SEBAGAI LANDASAN FILOSOFIS KEPEMIMPINAN TRANSFORMATIF DALAM MANAJEMEN PENDIDIKAN ISLAM MODERN - Naj’ma; Ahmad Barizi (STKIP Subang, 2026)
Strong and value-oriented leadership is one of the key determinants of successful management in Islamic educational institutions amid the challenges of the modern era. This study examines the concept of Al-Madinah Al-Fadilah (The Virtuous City) proposed by Al-Farabi as a philosophical foundation for transformative leadership in contemporary Islamic education management. The leadership crisis occurring in various Islamic educational institutions in Indonesia serves as the background for the importance of exploring authentic philosophical foundations rooted in the Islamic intellectual tradition. Through his work, Ara' Ahl Al-Madinah Al-Fadilah, Al-Farabi (872-950 CE) offers a comprehensive concept of leadership grounded in reason and justice, and oriented toward the attainment of true happiness (al-sa'adah). This study employs a qualitative method based on library research with a philosophical-analytical approach, examining a range of relevant literature. The findings indicate that the concept of Al-Madinah Al-Fadilah closely aligns with the four dimensions of transformative leadership proposed by Burns and Bass, namely Idealized Influence, Inspirational Motivation, Intellectual Stimulation, and Individualized Consideration. Moreover, this concept extends beyond these four dimensions by introducing a transcendental dimension oriented toward al-sa'adah as the ultimate goal of leadership. These findings offer practical implications, including strengthening the role of school principals as visionary and transformative leaders, developing value-based organizational culture, and fostering decision-making processes that balance rationality and spirituality.